Board characteristics and firm performance - Väätäinen, Lauri Johannes (My University, 2020)
Lack of good corporate governance is often stated as one of the main reasons for the latest financial crisis and collapses of big multinational companies. At the same time trends in privatization of firms, technology development and mobilization of capital have highlighted the need for better monitoring and governance of the business. Since board of directors are the main deciding part of the company it is important to study how different attributes and characteristics of the board impact on the financial performance of the firm. In this study, characteristics of board size, diversity, independence, affiliations and experience are studied in the sample of S&P500 companies during the period of 2009-2017. The main goal of the study is to discover if some of the board characteristics have significantly negative or positive impact on firm performance and can hereby increase the efficiency in the company and modernize possibly outdated structures in the board. Previous studies in the area of board characteristics have presented contradictory findings depending on the time frame and studied market. Therefore, wider theoretical understanding makes the topic important to study. As main findings of the paper, the thesis finds that S&P500 companies are lacking diversity, but diversity in the boardrooms has increased steadily among years. Board diversity and board experience are two characteristics which have positive impact on Tobin’s Q and return on assets. For other independent variables, the thesis did not find significance. However, even though the impact of diversity is positive it is important to understand that diversity itself is unlike to increase performance. Similarly, increasing only experience does not guarantee increase in performance. As a conclusion, this thesis suggests to keep in mind also other factors and limitation of endogeneity when finding the optimal level of board.
Keywords: boards of directors; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance